Education On Optimization Of Referral System For Cardiovascular Emergency Handling: Training And Simulation For Health Workers - Kurniawan, Rudi Erwin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2024)
Education on optimizing the referral system for cardiovascular emergencies is crucial for healthcare workers to improve the quality of medical services. This community service program aims to enhance healthcare workers' knowledge and skills through training and scenario-based simulations. The methods used include interactive lectures, workshops, and emergency simulations. Evaluations were conducted using pre-tests and post-tests to assess participants' knowledge improvement. The results showed a significant increase in participants' understanding and skills in handling cardiovascular emergency referrals. In conclusion, this training contributes to the readiness of healthcare workers in providing fast and accurate referral services. Additionally, the education provided increases awareness among healthcare workers regarding the importance of coordination between healthcare facilities to ensure optimal patient care. The implementation of this program is expected to serve as a model for improving a more efficient referral system, particularly in cardiovascular emergency cases.